Research and application of automatic production technology of fully mechanized longwall working face - Donghui LIAN; Ruifu YUAN; Kefei CUI; Xiang MA; Penghui YUAN; Kun PAN (Meitan kexue jishu, 2025)
The five procedures in a fully mechanized Longwall working face is coal cutting, coal loading to convey, coal convey out of the Longwall working face, roof supporting and goaf disposal. The fully mechanized mining face equipped with intelligent equipment should to cooperate under the program's control to complete the five procedures automatically. For different conditions of the Longwall working face, it is necessary to design the detailed technological process such as automatic operation of shearer to cut coal, automatic action of supports following the shearer. According to the functional characteristics of the intelligent equipment for the fully mechanized Longwall working face, four kinds of automatic production processes suitable for different coal seam conditions were put forward. For the flat coal seam and simple geological conditions, the automatic cutting process of the shearer with 14 steps and the automatic following process of the supports with 9 steps were designed, which solved the problem of automatic end feed cutting at the two ends of Longwall working face, and dramatically improved the production efficiency. Given the complex conditions of inclined coal seam, high inclination coal seam, and extremely thick steep coal seam, the automatic cutting process of midsection bevel feed, single-section cutting process of reverse feed at the end, and midsection bevel feed of shearer with ranging were proposed respectively. The application in many mines has dramatically improved the utilization rate of intelligent equipment automation and achieved in reducing personnel and improving efficiency, which has significant reference value for similar conditions of intelligent fully-mechanized Longwall working face to design and application of the production process.